Detection of palm oil adulteration in ghee using gas chromatography - Hazra, Tanmay; Sudheendra, CVK; Ahuja, Kunal Kumar; Sindhav, Rohit G; Ramani, Vimal M (Indian Journal of Dairy Science, 2020)
Ghee, is clarified butter or anhydrous milk fat, has an integral relation with Indian culinary culture. Due to the importance and seasonal decline in the production; unscrupulous traders tend to add cheap vegetable oils like palm oil in ghee. The composition of milk fat and oil vary in terms of fatty acids. Milk contains mainly short and medium chain fatty acids whereas vegetable oil contains long chain fatty acids. Due to different fatty acids composition between milk fat and palm oil, we tried to exploit this fatty acids difference to identify the adulteration of palm oil in ghee, using Gas chromatography. Study suggested that due to palm oil adulteration in ghee, the concentration of short chain fatty acids get decreased and long chain saturated and unsaturated fatty acids showed an increase. In addition to the above, change was also observed in the ratio of the total of saturated fatty acids to unsaturated fatty acids. Fatty acids analysis could be very effective for the detection of palm oil adulteration in ghee to the tune of 5 %. Our current study suggested that fatty acids study was able to detect foreign fat like palm oil in milk fat but this study is not suitable to confirm the type of foreign fat in milk fat or ghee.